2003
DOI: 10.1093/jb/mvg137
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptosis-Inducing Protein Kinase DRAK2 Is Inhibited in a Calcium-Dependent Manner by the Calcium-Binding Protein CHP

Abstract: Calcineurin homologous protein (CHP) is an EF-hand Ca(2+)-binding protein capable of interacting with various cellular proteins including Na(+)/H(+) exchangers, kinesin-related proteins, and apoptosis-inducing protein kinase DRAK2. We investigated the role of CHP on the DRAK2 protein kinase in vitro. CHP significantly reduced (approximately 85% inhibition) the kinase activity of DRAK2 for both autophosphorylation and phosphorylation of exogenous substrate (myosin light chain). The inhibitory effect of CHP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…The CHP1-induced inhibitory effect was Ca 2ϩ dependent whereas the binding between CHP1 and DRAK2 was not (65). This shows that the inhibition of the kinase activity by CHP1 is not due to simple CHP1-DRAK2 association and that the CHP1-DRAK2 complex association and dissociation with Ca 2ϩ may cause a conformational switch between an inactive and active state.…”
Section: Regulation Of Gene Transcription and Nuclear Functionmentioning
confidence: 90%
“…The CHP1-induced inhibitory effect was Ca 2ϩ dependent whereas the binding between CHP1 and DRAK2 was not (65). This shows that the inhibition of the kinase activity by CHP1 is not due to simple CHP1-DRAK2 association and that the CHP1-DRAK2 complex association and dissociation with Ca 2ϩ may cause a conformational switch between an inactive and active state.…”
Section: Regulation Of Gene Transcription and Nuclear Functionmentioning
confidence: 90%
“…71 Furthermore, several kinases and phosphatases are found to regulate ezrin/ radixin/moesin protein phophorylation, 19,61,72-76 and CHP1 is known to regulate protein kinase or phosphatase activity. 46,47 In conjunction, these possible mechanisms render the model of how CHP1 affects ezrin activation very complex, and extensive studies are required to address it.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In contrast, several studies reported a Ca 2+ -modulated interaction of CHP1 and CHP2 with their targets, suggesting that these CHPs might act as Ca 2+ -sensor proteins. 1 For instance, Ca 2+ is required for the interaction between rat CHP1 and the motor protein Kinesin-like protein 1Bß2 (KIF1Bß2) 15 ; CHP1 inhibits death-associated protein kinase-related apoptosis inducing protein kinase 2 (DRAK2) in a Ca 2+ -dependent manner 16 ; Ca 2+ is important for the activation of calcineurin A by CHP2 17 and for the complex formation of CHP2 with the cytoplasmic region (amino acid residues 515-545) of NHE1. 7 The interaction between CHPs and NHE1 is of particular interest, as NHE1 is an important regulator of intracellular pH homeostasis and cell volume.…”
Section: Introductionmentioning
confidence: 99%